Effectiveness of a Walking Group Intervention to Promote Physical Activity and Cardiovascular Health in Predominantly Non-Hispanic Black and Hispanic Urban Neighborhoods: Findings From the Walk Your Heart to Health Intervention. (June 2015) - Schulz, Amy J.; Israel, Barbara A.; Mentz, Graciela B.; Bernal, Cristina; Caver, Deanna; DeMajo, Ricardo; Diaz, Gregoria; Gamboa, Cindy; Gaines, Causandra; Hoston, Bernadine; Opperman, Alisha; Reyes, Angela G.; et al.
Objectives. The purpose of this study was to evaluate the effectiveness of the Walk Your Heart to Health ( WYHH ) intervention, one component of the multilevel Community Approaches to Cardiovascular Health: Pathways to Heart Health (CATCH:PATH) intervention designed to promote physical activity and reduce cardiovascular risk among non-Hispanic Black and Hispanic residents of Detroit, Michigan. The study was designed and implemented using a community-based participatory research approach that actively engaged community residents, health service providers and academic researchers. It was implemented between 2009 and 2012. Method. WYHH was a 32-week community health promoter–facilitated walking group intervention. Groups met three times per week at community-based or faith-based organizations, and walked for 45 to 90 minutes (increasing over time). The study used a cluster randomized control design to evaluate effectiveness of WYHH, with participants randomized into intervention or lagged intervention (control) groups. Psychosocial, clinical, and anthropometric data were collected at baseline, 8, and 32 weeks, and pedometer step data tracked using uploadable peisoelectric pedometers. Results . Participants in the intervention group increased steps significantly more during the initial 8-week intervention period, compared with the control group (β = 2004.5, p = .000). Increases in physical activity were associated with reductions in systolic blood pressure, fasting blood glucose, total cholesterol, waist circumference and body mass index at 8 weeks, and maintained at 32 weeks. Conclusion . The WYHH community health promoter–facilitated walking group intervention was associated with significant reductions in multiple indicators of cardiovascular risk among predominantly Hispanic and non-Hispanic Black participants in a low-to-moderate income urban community. Such interventions can contribute to reductions in racial, ethnic, and socioeconomic inequities in cardiovascular mortality.